Stellaria multipartita (Caryophyllaceae), a new species from Chongqing, China - Song, Yan-Feng; Li, Meng; Xu, Bo; Chen, Shui-Fei; Chen, Lin; Xie, Chun-Ping (Phytotaxa, 2020)
Stellaria multipartita sp. nov. (Caryophyllaceae) from Chongqing, China, is described and illustrated based on morphological and molecular data. The new species is similar to S. radians by the palmately fimbriate petals with more linear divisions. Different characters are: shape of the leaves (oblong-triangular to ovate-triangular vs. oblong-lanceolate to ovate-lanceolate in S. radians), petals (10–12-cleft vs. 5–7-cleft in S. radians), and seeds (with mamillate ornamentation vs. scrobiculate ornamentation in S. radians). A molecular phylogenetic analysis supports the recognition of Chongqing population as a new species for science.